The patient safety in the primary health care. An activity that could be overlooked? (2018)
Identication of the safety risks to the patient during the primary health care is usually carried out in the same way as the hospital clinical management, without taking into account that different risks are involved in either case. In the same vein, in Colombia there is not any public policy or regulatory guidelines specic to this sector, intended to demand the involved actors the use of standardized systematic instruments to record, report and analyze the adverse events in the primary health care. e big challenge to the Social Security General System for Health is to provide both a policy and the appropriate tools to undertake great transformations. It implies the implementation of a Comprehensive Health Care Policy, paying special attention to the primary health care, focusing on both the health promotion and disease prevention, and ensuring an environment to favor the patient safety during the health care services. © 2018 Pontificia Universidad Javeriana. All rights reserved.